New STS molecular markers for assessment of genetic diversity and DNA fingerprinting in hop (Humulus lupulus L.) - Patzak, Josef; Vrba, Lukás; Matousek, Jaroslav (Genome, 2007)
Molecular markers have been increasingly used in genetic studies of crop species for their applicability in breeding programs. In this work, we report on the development of new sequence-tagged site (STS) markers based on sequence information from several identified hop (Humulus lupulus L.) genes. We demonstrate the usefulness of these STS markers and compare them to SSRs for identifying hop genotypes and estimating genetic diversity in a collection of 68 hop cultivars from around the world. We found 3 individual gene variants (A, B, C) of the chs_H1 gene in this collection. The most frequent gene variant, B (AJ304877), was not detected in Mt. Hood, Glacier, and Horizon (US) cultivars. Gene variant A came from an American germplasm through wild hops. We found length polymorphism in intron 1 of the chs2 gene, and 4 different amplified markers were detected in PCRs. The chs3 gene was found in only one third of the cultivars. None of the variants of the studied CHS genes were found in Humulus japonicus. We detected 5 major gene variants of DNA-binding protein in the collection of H. lupulus cultivars and 2 others in H. japonicus. We also found 3 individual gene variants of an endochitinase gene. The distribution of gene variants did not correlate with any resistance. We proved that developed STS markers can be successfully used for the analysis of genetic diversity and can substitute and supplement SSR markers in hop.
Keywords: sekvence nukleotidů; Sequence Homology, Nucleic Acid; Genome, Plant; genom rostlinný; genetická variace; Crosses, Genetic; fylogeneze; Phylogeny; DNA fingerprinting; molekulární sekvence - údaje; DNA Fingerprinting; sekvenční homologie nukleových kyselin; Sequence Tagged Sites; DNA Primers; sekvenční seřazení; DNA rostlinná; místa se sekvenční adresou; DNA, Plant; křížení genetické; DNA primery; Humulus; Molecular Sequence Data; Base Sequence; Genetic Variation; Sequence Alignment